The TAPin electronic libraries project and the experience at the University of Birmingham - Tracy K. Mulvaney (Information Research: An International Electronic Journal)
The TAPin Project and its implementation at the University of Birmingham is described. Local issues and key features of a hybrid approach to Networked Learner Support are addressed. The methods of NLS adopted included electronic mail and the Internet. The key role in NLS played by subject librarians is stressed. Transfer of skills to learners by means of targeted individual training and a web guide is discussed.